PERILAKU INFORMASI DAN PREFERENSI UNIVERSITAS PADA GENERASI MILENIAL - Suci, Afred; Nanda, Satria Tri (Jurnal Daya Saing, 2018)
Digital era has shifted the role and information search behavior of selecting university. This study aims to map the role of influencer and decision maker and so as to analyze millennial student’s information search behavior for private universities. Respondent consists of 200 new students in seven private universities located in Riau Province, Indonesia. Data analyzed by using descriptive and chi-square for non-parametric statistic. Study reveals that millennial students autonomously become either prime influencer or decision maker in selecting campus destination. The main information source for millennial students are digital platforms and their peer community. There is no significant relationship between student's background and role of influencer. Meanwhile, student’s area of origin and their working status have a significant relationship with the role of final decision making. On the contrary, parents’ domicile, previous high school, and choice of study department have no significant relationship with the role of final decision making. The most important information for private university applicants are the availability and completeness of campus facilities, detail of tuition fee, and information of scholarship opportunities.